Effect of methylprednisolone use on the rotator cuff in rats: biomechanical and histological study - Gustavo Vinícius Ghellioni; Lucas Souto da Silva; Anna Paula Piovezan; Rafael Olívio Martins (Revista Brasileira de Ortopedia, 2015)
OBJECTIVE: To evaluate the influence of treatment with different doses of methylprednisolone on the mechanical resistance and possible histological alterations of the rotator cuff tendon in rats.METHODS: Male Wistar rats were divided randomly into four treatment groups: sham, vehicle or 0.6 mg/kg or 6.0 mg/kg of methylprednisolone. Changes to mechanical resistance (in N) and histological parameters (fibrillar appearance, presence of collagen, edema and vascular proliferation) of the rotator cuff tendon were evaluated. The analyses were conducted after administration of one treatment (24 h afterwards), two treatments (7 days afterward) or three treatments (14 days afterwards), into the subacromial space.RESULTS: Seven and fourteen days after the treatments were started, it was found that in a dose-dependent manner, methylprednisolone reduced the mechanical resistance of the rotator cuff tendon (p < 0.05 in relation to the vehicle group). Modifications to the histological parameters were observed on the 7th and 14th days after the first infiltration, especially regarding the presence of collagen and vascular proliferation, for the dose of 0.6 mg/kg of methylprednisolone, and also regarding the presence of collagen, edema and vascular proliferation for the dose of 6.0 mg/kg of corticoid.CONCLUSION: The results obtained demonstrated a relationship between methylprednisolone use through infiltration into the subacromial space and reduction of the mechanical resistance of and histological modifications to the rotator cuff tendon in rats.